Development of rotary Wankel devices for hybrid automotive applications. (15th December 2019) - Sadiq, Ghada A.; Al-Dadah, Raya; Mahmoud, Saad
Highlights: Vehicle's kinetic energy through braking using MATLAB is investigated. Wankel and piston compressor's performance is compared. Different vehicle speeds, weights, braking times, and tank sizes are studied. Maximum system energy saving efficiency of 77% is achieved. Instantaneous system efficiency of about 85% is obtained. Abstract: Several attempts have been made to reduce greenhouse gas emissions (GHG) employing hybridization. Compressed air-electrical hybrid system is a promising technology which can be used to reduce the environmental impact of the automotive industry. In cities and urban areas, vehicle's kinetic energy through braking can be converted to pressurized air which can be stored in a storage tank for reuse to operate the vehicle during starting, cruising, and acceleration. In this study, an efficient expander and compressor are developed using a Wankel device for the compressed air-electric hybrid vehicle. Volumetric Wankel rotary expander and compressor are essential devices for power generation in compressed air energy storage (CAES) system and compressed air hybrid engine powered by the braking energy system leading to a significant decrease in GHG emissions. Compared with conventional expanders and compressors, Wankel expander and compressor have significant advantages due to its compactness, lower vibration, noise, and cost. Different parametric studies have been carried out with different vehicle initial speeds (80, 60, 40) km/h and weights (500, 750, 1000) kg, various braking times (2, 3, 5, 7) s, and finally three different tank sizes (20, 35, 50) l using mathematical modelling MATLAB software. The maximum system energy-saving efficiency achieved was around 77% and instantaneous system efficiency of about 85% at an initial vehicle speed of 80 km/h, braking time of 3 s, and vehicle weight of 750 kg and compressed air tank of 35 l.